Effect of OM chanting on working memory among school-going children (Indian Journal of Traditional Knowledge (IJTK), 2025)
Adolescents today face increasing cognitive challenges due to over exposure to digital media and reduced engagement in activities that help improve their cognitive functions such as working memory. Working memory plays a vital role in learning, attention and academic performance, yet interventions targeting its improvement in healthy children are limited. This study aimed at observing the effect of OM chanting on working memory amongst school children. 67 students of eighth-grade, aged between 13-15, who were willing to participate were recruited for the study and separated into two groups i.e., experimental (n=34) and control group (n=33). The intervention group was asked to chant 21 rounds of OM chanting during the morning assembly and before going home i.e., twice a day. Working memory was measured using the digit span test, data was collected before and after the 4-weeks intervention period. Digit span test comprises two subtests. Digit span forward (DS-F) examines short-term memory, while digit span backward (DS-B) measures working memory. In the intervention group, a significant improvement was seen in both the tests, while there was no significant change in the control group. Paired sample t-test was applied to measure the changes between pre and post data of both the test. p-value for DS-F in experimental group was 0.001 and for DS-B is 0.003. From these results we can infer that OM chanting has a positive and calming effect on our brain with increase in working memory capacity of students, which helps in retention and concentration, and thus can improve their academic performance.